Transient exposure to androgens induces a remarkable self-sustained quiescent state in dispersed prostate cancer cells. Issue 9 (3rd May 2017) - Bui, Anh Thu; Huang, Meng-Er; Havard, Maryline; Laurent-Tchenio, Fanny; Dautry, François; Tchenio, Thierry
ABSTRACT: Cellular quiescence is a reversible cell growth arrest that is often assumed to require a persistence of non-permissive external growth conditions for its maintenance. In this work, we showed that androgen could induce a quiescent state that is self-sustained in a cell-autonomous manner through a "hit and run" mechanism in androgen receptor-expressing prostate cancer cells. This phenomenon required the set-up of a sustained redox imbalance and TGFβ/BMP signaling that were dependent on culturing cells at low density. At medium cell density, androgens failed to induce such a self-sustained quiescent state, which correlated with a lesser induction of cell redox imbalance and oxidative stress markers like CDKN1A. These effects of androgens could be mimicked by transient overexpression of CDKN1A that triggered its own expression and a sustained SMAD phosphorylation in cells cultured at low cell density. Overall, our data suggest that self-sustained but fully reversible quiescent states might constitute a general response of dispersed cancer cells to stress conditions.